PENGARUH BIOCHAR SEKAM PADI DAN KOMPOS TERHADAP C-ORGANIK, N-TOTAL, C/N TANAH, SERAPAN N, DAN PERTUMBUHAN TANAMAN JAGUNG DI ULTISOL - Geraldine Abel; Retno Suntari; Ania Citraresmini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The maize crop is an important commodity other than rice in Indonesia. Maize production reached 30 million tons in 2018. Efforts that can be made to increase maize production on Ultisols in Indonesia is by the application of biochar rice husk and compost. Biochar that has a high affinity for nutrients does not experience decay in the soil for decades, while compost can improve soil chemical properties by increasing nutrient content. The purpose of this study was to analyze the effect of the application of a combination of rice husk biochar and compost on soil chemical properties, N uptake, and growth of maize on an Ultisol. This study was conducted with six treatments. The results showed that the application of a combination of rice husk biochar and compost had an effect on increasing the C-organic and N-total in soil, but it did not affect the C/N of the incubated soil. Application of a combination of 8 t rice husk biochar ha-1 and 30 compost ha-1 significantly improved plant height, dry weight, and N uptake of maize plants.